Environmental risk assessment of toxicity exposure: High-throughput expression profiling - Hong, Ji Young; Yu, So Yeon; Ahn, Jeong Jin; Kim, Seol Young; Kim, Gi Won; Kim, Youngjoo; Son, Sang Wook; Hwang, Seung Yong (Biochip journal, 2016)
Recently, volatile organic compounds (VOCs) in outdoor air pollution have led to major public health problems and the identification of specific minimally invasive biomarkers for assessing environmental toxicant exposure has become increasingly important. However, research into the human health effects of inhalation exposure to VOCs remains insufficient. Using a microarray based approach, we identified and validated characteristic mRNA expression profiles in the human whole blood of workers exposed to VOCs (toluene, ethylbenzene, and xylene), which were then compared with genomic level expressions in workers not exposed to the toxicants. We surveyed 141 workers working in a chemical production factory, of which 66 were not exposed to VOCs. We identified 4384 characteristic discernible exposure indicator mRNAs for toluene, 1296 for ethylbenzene, and 5821 for xylene. Using these, we were able to discern those subjects from the control group to a higher accuracy, sensitivity, and specificity than when using urinary biomarkers. The results showed that altered levels of mRNA can be a reliable, novel, and minimally invasive biological indicator of occupational exposure to VOCs. Future research directions should consider the adverse effects of exposure to VOCs on epigenetic regulation.